STUDI BANDING EMAIL FORENSIC TOOLS - Tulus Hadianto; Widi Prasetyo; Rizal Broer Bahaweres (STUDIA INFORMATIKA: JURNAL SISTEM INFORMASI, 2017)
Over the last few decades, email has become a carrier source for transporting spam and malicious content. The Email Network is also a major source of criminal activity on the Internet. Computer Forensics is a systematic process for storing and analyzing email stored on a computer for the purpose of proof in legal proceedings and other civil matters. Email analysis is challenging because it is not only used in various fields that can be done by hackers or malicious users, but also the flexibility of composing, editing, deleting email using offline (eg, MS Outlook) or online email (eg Webmail) applications. To anticipate this, an approach is taken using email forensic tools to understand the extent to which these tools will be useful for detecting and performing appropriate forensic analysis. In this paper, we conducted a comparative study of a set of common features to compare and compare five popular opensource tools forensic email. The study found that all forensic email tools are not similar, offering all types of facilities. Combining these tools allows analysis to get detailed information in the field of forensic email.